On the Optimal Design of a Financial Stability Fund - Ábrahám, Árpád; Carceles-Poveda, Eva; Liu, Yan; Marimon, Ramon (Review of Economic Studies, 2026)
We develop a model of a Financial Stability Fund (the “Fund” henceforth) for a union of sovereign countries. By design, the contract prevents country defaults, as well as undesired expected losses, which in a union translate into excessive risk mutualizations. A participant country has greater ability to borrow and share risks than using sovereign debt financing. The Fund contract also provides better incentives for the country to reduce endogenous risks. These efficiency gains arise from the ability of the Fund to offer long-term contingent financial contracts, subject to limited enforcement and moral hazard constraints. We develop the theory and quantitatively compare the constrained-efficient Fund economy with an incomplete markets economy with default. We calibrate our economy to the euro area “stressed countries” in the debt crisis (2010–2). Substantial welfare gains are achieved, particularly in times of crisis. The Fund is, in fact, a risk-sharing, crisis prevention and resolution mechanism, which transforms the participant countries’ defaultable sovereign debt into the union’s safe assets. In sum, our theory can help to improve current official lending practices and, for example, to eventually design a European Fiscal Fund.